Desenvolvimento de sensores fotoeletroquímicos autoalimentados para determinação de ácido tânico - SILVA, Fernanda Gabrielle Soares da (2021)
The present work describes the development of two photoelectrochemical systems for the determination of tannic acid (TA) since the development of analytical methods capable of detecting and quantifying this substance becomes essential. The self-powered cells were composed of a photoanode and a photocathode separated in two chambers to generate output power with adequate incidence of visibre light from a commercial LED lamp in order to allow the TA detection process. The construction of photoelectrochemical sensors was carried out by preparing photoactive materials based on oxides and chalcogenides (zinc oxide, titanium oxide, copper oxide, copper sulfide and cadmium sulfide) through the techniques of electrodeposition, chemical deposition and the method of printing material onto glass electrodes covered with fluorine-doped tin oxide (FTO) known as “doctor blade”. The first work is a self-powered photoelectrochemical system based on a CdS/TiO2/FTO photoanode and a CuS/FTO photocathode for the determination of TA. Under optimized conditions, the photoelectrochemical system showed a linear response range for AT from 10 μmol L-1 to 500 μmol L-1 and a detection limit of 5 μmol L-1. The results also showed that the constructed system is a promising alternative for the determination of TA in orange juice samples. The second work describes the development of a self-powered photoelectrochemical system for the determination of TA, exploring simultaneously the process of sensitization of a TiO2/FTO photoanode by the analyte (TA) and a Cu2O/ZnO/FTO photocathode for water reduction. The principle of the self-powered photoelectrochemical cell is based on the reduction of water in the cathode chamber over the Cu2O/ZnO/FTO photocathode while the TA is oxidized in the anode chamber in order to generate an output power in the cell that depends on the concentration of TA in the compartment anodic. Under optimized conditions, the cell showed a wide range of linear response for TA from 1 μmol L-1 to 500 μmol L-1, demonstrating that the capacity of the proposed system to generate energy can be modulated by the concentration of TA. Thus, the developed systems proved to be low cost, easy to operate, sensitive and selective methodologies for the determination of TA without the need for an external power source to oxidize the analyte.